A wide-band current-mode OTA-based analog multiplier-divider - Kaewdang, Khanittha; Fongsamut, Chalermpan; Surakampontorn, Wanlop (My University, 2003)
A current-mode analog multiplier-divider circuit that realized through the use of operational transconductance amplifiers (OTAs) is proposed in this paper. The proposed scheme is realized in such a way that employs only OTAs as active circuit elements and does not require external passive circuit elements. The circuit is simple and can be easily constructed from commercially available IC. The circuit is temperature compensated and the circuit bandwidth is approximately close to the bandwidth of pnp current mirrors or fTP/2. The performance of the multiplier-divider circuit is discussed and confirmed by simulation results.